1990
DOI: 10.1038/clpt.1990.145
|View full text |Cite
|
Sign up to set email alerts
|

Oral morphine in cancer pain: influences on morphine and metabolite concentration

Abstract: One hundred fifty-one patients with chronic cancer pain were studied during chronic treatment with oral morphine. Plasma concentrations of morphine and metabolites (M3G and M6G) were measured. The ratio of plasma morphine to metabolites was not affected by dose. Generalized linear interactive modeling analysis using morphine dose, age, sex, renal and hepatic dysfunction, and concomitant medication as explanatory variables accounted for 70% of the variance in plasma concentrations of morphine, morphine-3-glucur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(79 citation statements)
references
References 0 publications
5
73
0
1
Order By: Relevance
“…The ratio of morphine to M6G concentrations ranged from 1 : 5.5 to 1 : 6.7, which is in agreement with previous studies (15,16).The high number of patients with undetectable plasma morphine concentrations prior to the morning drug dosing is probably due to the low daily CR opioid dose in these patients (mean daily morphine dose 75 mg) since three of these patients had very low oxycodone concentrations, too. In previous clinical studies of cancer patients, it has been found that even low daily doses of CR morphine have resulted in measurable plasma morphine concentrations (17,18) but the assay limit for morphine has been lower (1 ng:ml) (19) than in the present study (5 ng:ml).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The ratio of morphine to M6G concentrations ranged from 1 : 5.5 to 1 : 6.7, which is in agreement with previous studies (15,16).The high number of patients with undetectable plasma morphine concentrations prior to the morning drug dosing is probably due to the low daily CR opioid dose in these patients (mean daily morphine dose 75 mg) since three of these patients had very low oxycodone concentrations, too. In previous clinical studies of cancer patients, it has been found that even low daily doses of CR morphine have resulted in measurable plasma morphine concentrations (17,18) but the assay limit for morphine has been lower (1 ng:ml) (19) than in the present study (5 ng:ml).…”
Section: Discussionsupporting
confidence: 79%
“…In cancer patients, however, the steady-state plasma morphine levels may be affected by the disease or other factors (e.g. chronic constipation) that can in uence the absorption of CR tablets (15).…”
Section: Discussionmentioning
confidence: 99%
“…No significant correlation was found between the 6-glucuronidation of ethylmorphine and morphine. The ratios of morphine and its glucuronides were similar to those observed after administration of morphine [31,32]. No difference was found between subjects with high or low urinary recoveries of morphine plus morphine-glucuronides with respect to the morphine-3-glucuronide/morphine-6-glucuronide ratio.…”
Section: Discussionsupporting
confidence: 55%
“…In this respect the ratio of M3G:M6G found in neonates is markedly lower than previously demonstrated in adults or children. In adults, chronic oral morphine treatment produces variable plasma ratios of M3G:M6G, with reported mean ratios of 10:1 (Hand et al, 1987), 6:1 and 5:1 (McQuay et al, 1990). A study of a single intravenous dose of morphine in adults found a plasma ratio of M3G:M6G of 8.5 (Hasselstrom et al, 1990).…”
Section: Discussionmentioning
confidence: 99%